Controllable Assembly and Dehydrogenation Catalysis Activity of Urchinlike FeNi–Ru(tips) Amorphous Alloy Hierarchical Nanostructures. Issue 4 (19th March 2013) - Sun, Yuzhen; Wen, Ming; Wu, Qingsheng; Wu, Qingnan
Abstract Novel, urchinlike FeNi–Ru(tips) hierarchical‐structured nanospheres (≈9.17 µm) were constructed through a controllable assembly process. Offering large surface areas and macropores as well as more active sites, this special structured catalyst can greatly facilitate reactant diffusion and transport to promote reactivity. By combining the advantages of Ru and FeNi nanomaterials, the resultant urchinlike FeNi–Ru(tips) nanospheres exhibit excellent catalytic activity with the dehydrogenation rate of 2245.87 mL min−1 g−1 toward the hydrolytic dehydrogenation of aqueous NaBH4 under ambient atmosphere at room temperature, in which Fe19Ni76–Ru5 shows the best dehydrogenation reactivity with low activation energy (41.57 kJ mol−1). Additionally, these new structured nanoalloys present controllable ferromagnetic behavior by means of adjusting the molar content of Fe, Ni, and Ru.